The Epigraphic Survey - University of Chicago - Oriental Institute (2006)
[Dt.:] Die Website beinhaltet Informationen über das "The Epigraphic Survey"-Projekt des Oriental Institute der Universität Chicago, welches die Inschriften und Reliefszenen der größeren Tempel und Gräber in Luxor dokumentiert und konserviert. Auf der Seite findet man Informationen zum Projekt und zu Publikationen, Artikel und Berichte sowie Bildmaterial. - [Engl.:] This web site contains information about the "Epigraphic Survey" project of the Oriental Institute of the Chicago University. It's aim are the publication and conservation of the inscriptions and relief scenes on major tempels and tombs at Luxor. On the web site you can find information about this project as well as publications, articles, reports and photographs.